Library Promotion Strategy in the Covid-19 Pandemic Period at Dinas Perpustakaan dan kearsipan Kabupaten Serdang Bedagai - Syam, Abdi Mubarak (Pena Cendekia Insani, 2022)
This study aims to determine the library's strategy in carrying out library promotions during the covid-19 pandemic as well as the obstacles felt by libraries and also how to overcome the obstacles that occur. The method used in this study is a qualitative method using a descriptive approaches. The data collection techniques used in this study were interviews, observations and documentation. The results of this study indicate that the library promotion strategy during the covid-19 pandemic carried out by libraries is by holding library socialization, mobile libraries, promotion through social media, making advertisements, collaborating with other parties and making rewards (gifts). While the obstacles that occur are network limitations and budget funds. The way to overcome the perceived obstacles is the installation of wi-fi.